2021
DOI: 10.3390/su13063227
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Effect of Occupant Behavior-Related Factors in Office Buildings Based on the DNAS Theory

Abstract: Occupant behavior is acknowledged as a main contribution to building energy consumption. Many efforts have been devoted to identifying the impact of occupant behaviors on building energy consumption. However, the lack of understanding of the interaction effects among occupant behavior-related factors, to some extent, can lead to inaccurate results. To decode these complex interactions, this study was conducted to investigate the interaction effects of occupant behavior-related factors. A survey based on the Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 70 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…The interdisciplinary data collection through the questionnaire contributes to transforming the discovered knowledge into behavior-based energy efficiency solutions, taking into account not only energy metrics and physical properties of building characteristics but also the contextual aspects related to the energy and profile of the OB within the workplace. Most research related to OB defines it based on occupan t movements [40][37] and control actions on the equipment or control devices of the building [14] [9]. Likewise, it has been indicated that they can be divided into two aspects: Occupancy, which refers to the rate within the building; and occupant control behaviors on building devices, including windows, doors, shades, air conditioning terminals, lights, and equipment (TVs, computers, printers, etc.).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The interdisciplinary data collection through the questionnaire contributes to transforming the discovered knowledge into behavior-based energy efficiency solutions, taking into account not only energy metrics and physical properties of building characteristics but also the contextual aspects related to the energy and profile of the OB within the workplace. Most research related to OB defines it based on occupan t movements [40][37] and control actions on the equipment or control devices of the building [14] [9]. Likewise, it has been indicated that they can be divided into two aspects: Occupancy, which refers to the rate within the building; and occupant control behaviors on building devices, including windows, doors, shades, air conditioning terminals, lights, and equipment (TVs, computers, printers, etc.).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, in other research [42], a group of buildings was classified by algorithms, where each group contained a very similar type of occupant behavior. In addition to the occupant behaviors described above by classification, [9][10] presented a DNAS theory to describe occupant behaviors. The DNAS theoretical framework provides a standardized way of representing occupant behaviors from four perspectives, namely drivers, needs, actions, and systems, Figure 1; that can be applied to guide behavior program design, implementation, and evaluation, and facilitate the integration of occupant behavior models with building simulation tools.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these standard assumptions sometimes do not fulfil user comfort and satisfaction [6,7]. Because people spend most of their time in buildings and interact with building systems to reach desired comfort, these interactions lead to different energy usage [8][9][10][11]. The impact of user actions on various systems, including cooling, heating, etc., has been tested many times [12][13][14].…”
Section: Introductionmentioning
confidence: 99%